AB0081 Reactive oxygen species inhibit catalytic activity of peptidylarginine deiminase. (15th June 2017) - Damgaard, D; Bjørn, ME; Nielsen, CH
Abstract : Background: Protein citrullination is catalysed by pepdidylarginine deiminase (PAD) and plays an important pathogenic role in anti-citrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), and possibly in other inflammatory diseases. PAD activity is dependent on calcium and reducing conditions. Objectives: To determine the ability of H2 O2 and reactive oxygen species (ROS) induced by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase to regulate PAD activity. Methods: Activity of recombinant human (rh) PAD2, rhPAD4 and PADs released from phorbol 12-myristate 13-acetate (PMA)-stimulated leucocytes was measured using an in-house PAD activity assay detecting citrullination of fibrinogen. PAD2 released from cells was measured using a luminex-based assay. The NADPH oxidase inhibitor diphenyleneiodonium (DPI) was used to inhibit ROS production in cells. Results: At concentrations above 40 μM, H2 O2 inhibited the catalytic activity of reduced rhPAD2 and rhPAD4. The inhibitory effect increased with increasing H2 O2 concentration, reaching complete abrogation at 600 μM. PMA-stimulated leucocytes showed markedly higher PAD activity following inhibition of ROS formation with DPI. At a concentration of 10, 000 μM, exogenously added H2 O2 inhibited the catalytic activity of PAD released from PMA-stimulated leukocytes. Conclusions: The ROS H2 O2 directly inhibits enzymatic activity of PAD, and generation of ROS by NADPH oxidase down-regulates the activity of PAD released from stimulated leucocytes. This mechanism may play an important role in preventing hypercitrullination of proteins and thereby generation of self-antigens in RA. Disclosure of Interest: None declared